Metformin Hydrochloride Loaded Mucoadhesive Microspheres and Nanoparticles for Anti-Hyperglycemic and Anticancer Effects Using Factorial Experimental Design - Kotha AA; Ahmad SU; Dewan I; Bhuiyan MA; Rahman FI; Naina Mohamed I; Reza MS (Dove Medical Press, 2023)
Amina Alam Kotha,1,* Shihab Uddin Ahmad,2,3,* Irin Dewan,2 Mohiuddin Ahmed Bhuiyan,2 Fahad Imtiaz Rahman,1 Isa Naina Mohamed,3 Md Selim Reza1 1Department of Pharmaceutical Technology, Faculty of Pharmacy, University of Dhaka, Dhaka, 1000, Bangladesh; 2Department of Pharmacy, School of Medicine, University of Asia Pacific, Dhaka, 1215, Bangladesh; 3Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Kuala Lumpur, 56000, Malaysia*These authors contributed equally to this workCorrespondence: Md Selim Reza, Department of Pharmaceutical Technology, Faculty of Pharmacy, University of Dhaka, Dhaka, 1000, Bangladesh, Email selimreza@du.ac.bd Isa Naina Mohamed, Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Jalan Yaacob Latif, Bandar Tun Razak, Cheras, Kuala Lumpur, 56000, Malaysia, Email isanaina@ppukm.ukm.edu.myBackground: Metformin hydrochloride (HCl) microspheres and nanoparticles were formulated to enhance bioavailability and minimize side effects through sustained action and optimized drug-release characteristics. Initially, the same formulation design with different ratios of metformin HCl and Eudragit RSPO was used to formulate four batches of microspheres and nanoparticles using solvent evaporation and nanoprecipitation methods, respectively.Methods: The produced formulations were evaluated based on particle size and shape (particle size distribution (PSD), scanning electron microscope (SEM)), incompatibility (differential scanning calorimetry (DSC), Fourier-transform infrared (FTIR)), drug release pattern, permeation behavior, in vivo hypoglycemic effects, and in vitro anticancer potential.Results: Compatibility studies concluded that there was minimal interaction between metformin HCl and the polymer, whereas SEM images revealed smoother, more spherical nanoparticles than microspheres. Drug release from the formulations was primarily controlled by the non-Fickian diffusion process, except for A1 and A4 by Fickian, and B3 by Super case II. Korsmeyer-Peppas was the best-fit model for the maximum formulations. The best formulations of microspheres and nanoparticles, based on greater drug release, drug entrapment, and compatibility characteristics, were attributed to the study of drug permeation by non-everted intestinal sacs, in vivo anti-hyperglycemic activity, and in vitro anticancer activity.Conclusion: This study suggests that the proposed metformin HCl formulation can dramatically reduce hyperglycemic conditions and may also have anticancer potential.Keywords: microsphere, nanoparticles, permeability, anti-hyperglycemic, anticancer